Videojournalism : - Kobre, Kenneth 1946- (Focal Press, 2012)
"The solo videojournalist must find a riveting story; gain access to charismatic characters who can tell their own tales; shoot candid clips; expertly interview the players; record clear, clean sound; write a script with pizzazz; and, finally, edit the material into a piece worthy of five minutes of a viewer's attention. Videojournalism addresses all of these challenges and more. [...] Opening chapters cover the foundations of mutlimedia storytelling, and then the book progresses to the techniques required to shoot professional video, record high quality sound and market the resulting product"--Back cover.